Biostratigraphy of Jurassic beds south of Prezid in Gorski Kotar - Dozet, Stevo; Šribar, Ljudmila (Geologija, 1981)
An interrupted succession of tbe Jurassic beds is well exposed south of Prezid in Gorski Kotar. In general different limestone and dolomite varieties succeed each other and some intraformational breccia and oolite intercalations occur here and there. The boundary between Triassic and Jurassic systems being transitional in its lithologic character could not be identified chronologically. The following zones have been determined clearly enough: Lithiotid zone (Middle Liassic), Mesoendothyra croatica (Lower Doggerian), Selliporella donzellii (Upper Doggerian), Macroporella sellii (Lower Malmdan), Clypeina jurassica (Upper Malmian). In the top of the latter a subzone is distinguished as Clypeina jurassica is associated there with Campbelliella milesi milesi.